2007
DOI: 10.1111/j.1365-2672.2007.03382.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial populations in acid mineral bioleaching systems of Tong Shankou Copper Mine, China

Abstract: Aims:  To understand the composition and structure of microbial communities in different acid mineral bioleaching systems, and to present a more complete picture of microbially mediated acid mine drainage production. Methods and Results:  In Tong Shankou Copper Mine, China, two samples (named K1 and K2) from two different sites with bioleaching were studied. A bacterial 16S rDNA library and an archaeal 16S rDNA library of the sample from each site were constructed by 16S rDNA polymerase chain reaction (PCR), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…To date, there are three recognized groups within the clade Leptospirillum based on 16S rRNA phylogeny: group I (Leptospirillum ferrooxidans), group II (Leptospirillum ferriphilum and "Leptospirillum rubarum"), and group III (Leptospirillum ferrodiazotrophum) (7)(8)(9). All three Leptospirillum groups have been observed in 16S rRNA gene surveys and metagenomic studies from acidic and bioleaching environments worldwide (5,(10)(11)(12)(13). Based on isolate characterization studies, all are iron-oxidizing chemoautotrophs, and two groups (groups I and III) are reported to be capable of nitrogen fixation (9,14).…”
mentioning
confidence: 99%
“…To date, there are three recognized groups within the clade Leptospirillum based on 16S rRNA phylogeny: group I (Leptospirillum ferrooxidans), group II (Leptospirillum ferriphilum and "Leptospirillum rubarum"), and group III (Leptospirillum ferrodiazotrophum) (7)(8)(9). All three Leptospirillum groups have been observed in 16S rRNA gene surveys and metagenomic studies from acidic and bioleaching environments worldwide (5,(10)(11)(12)(13). Based on isolate characterization studies, all are iron-oxidizing chemoautotrophs, and two groups (groups I and III) are reported to be capable of nitrogen fixation (9,14).…”
mentioning
confidence: 99%
“…Acidophilic Leptospirillum bacteria dominate this AMD system (15), other AMD systems (54), and bioleaching systems used for recovery of metals (19,53,86). These bacteria play pivotal roles in sulfide mineral dissolution because they are iron oxidizers (53,75), and ferric iron drives sulfide oxidation, leading to formation of metal-rich sulfuric acid solutions.…”
mentioning
confidence: 99%
“…Detection or quantification of the Ferroplasmaceae in these environments was done mostly using small subunit (SSU) rRNA-targeting analyses, such as 16S rRNA gene clone libraries' sequencing, amplified rRNA gene restriction analysis (ARDRA) profiling, real-time quantitative PCR, restriction fragment length polymorphism (RFLP) or fluorescence in situ hybridization (FISH), and oligonucleotide microarray analysis, all of which revealed the presence of these archaea in a number of pyritic/arsenopyritic, gold-arsenopyritic/chalcopyritic, and lead-, zinc-, and copper-containing mines across all continents (11,24,26,45,46,51,55,56,57,58). Clones related to the family Ferroplasmaceae have also been documented in further natural sulfide-rich ecosystems, e.g., in the snottites, i.e., the stalactite-like formations of microbial origin taken from the walls of Frasassi Cave and in the Rio Garrafo cave systems, both located in Italy, where acidic microenvironments were formed as a result of sulfide oxidation (38).…”
mentioning
confidence: 99%